Plerixafor‐based mobilization in pediatric healthy donors with unfavorable donor/recipient body weight ratio resulted in a better CD34+ collection yield: A retrospective analysis. Issue 1 (20th October 2020) - Zubicaray, Josune; Galvez, Eva; Sebastian, Elena; Molina, Blanca; González‐Vicent, Marta; Castillo, Ana; Ramírez, Manuel; Madero, Luis; Díaz, Miguel Angel; Sevilla, Julian
Abstract: Introduction: In order to propose risk‐adapted mobilization algorithms, several authors have tried to look for predictive factors of the CD34 + yield in healthy pediatric donors. Donor recipient body weight ratio (D/R ratio) was identified as one of the main variables related with the success to achieve the target cell dose for transplantation. According to this variable we modified the mobilization schedule. Material and methods: We report the results of 46 mobilizations and apheresis procedures performed in our center with unfavorable D/R ratio. Mobilization was attempted by the standard regime of G‐CSF (10 mcg/kg/24 hours) in 28 cases (60.9%), with high dose G‐CSF (10 mcg/kg/12 hours) in 9 cases (19.6%), and with plerixafor and G‐CSF single dose regime in 9 cases (19.6%). Results: CD34 + cell quantification before apheresis is closely related to CD34 + yield, being the only factor related to collected CD34 + cells (beta .71; P < .0001). The mobilization efficiency was higher in plerixafor group compared to the other two schedules ( P < .0001). By using plerixafor for mobilization, we achieved the target CD34 + cell dose of ≥2 × 10 6 /kg per recipient body weight in all cases with unfavorable D/R ratio. It was observed that 17.4% of cases that not reached the established target cell dose were located in the standard or high‐dose mobilization regimes. This difference is even greater for optimal collections (≥5 × 10 6 /kg), since of the 54.3% cases that did not reach this goal none was mobilized by plerixafor. Conclusion: Tailoring the mobilization regime we can reach the target cell dose, even in those cases with the worst D/R ratio.